Global applications of stable isotopes for identifying nitrate pollution sources in groundwater: a comprehensive review - Oubeid, Ahmed Mahmoud Ahmed; Hilal, Ismail; Kebd, Aminetou; Sadiki, Mohamed (Frontiers in Water, 2025)
As a critical resource for both livelihoods and economic progress, groundwater is increasingly endangered by nitrate contamination stemming from intensive agriculture, landfill leachates, wastewater effluents, soil nitrogen leaching, sewage discharge, and other anthropogenic influences. Stable isotopes (δ15N–NO₃−, δ18O–NO₃−, δ11B) have emerged as powerful tools to distinguish pollution sources, including synthetic fertilizers, animal manure, domestic wastewater, and atmospheric deposition. In regions with intensive agriculture and urban sprawl, nitrate concentrations frequently exceed safe thresholds, underscoring the need for precise source identification to guide mitigation strategies. While traditional vulnerability mapping elucidates contamination pathways, it often fails to resolve specific sources. The integration of multi-isotope tracers (e.g., δ11B with δ15N–NO₃−, δ18O–NO₃−) alongside hydrochemical data has emerged as an effective approach to address this gap, particularly in complex hydrogeological settings. While previous reviews have addressed nitrate contamination and isotope applications, this study adds value through its updated scope (2015–2025), global comparison, emphasis on multi-isotope integration, and the presentation of a unified framework and best practices for source identification. The findings highlight actionable insights for groundwater protection and advocate for the widespread adoption of isotopic tools in sustainable water management worldwide.